On the recognition of Passiflora hibiscifolia (Passifloraceae, section Dysosmia) - Svoboda, Harlan T. (Instituto de Ecología, A.C., 2018)
Background and Aims: Passiflora section Dysosmia is considered one of the most complicated groups in the passionflower genus, due in part to the difficulty of accurately delimiting taxa. One such example, currently recognized as Passiflora ciliata var. hibiscifolia, has undergone a series of nomenclatural changes based on varying taxonomic opinions since its circumscription in 1789. Few researchers have thus far objectively investigated the uniqueness of this taxon or its affinity with other similar taxa in the section. The objective of this study was to characterize the taxon currently known as P. ciliata var. hibiscifolia and provide evidence for its taxonomic recognition.Methods: Intensive morphological studies were carried out using 217 herbarium specimens, including type material, supplemented by 27 iNaturalist observations.Key results: The results show significant, consistent macro- and micromorphological differences between the taxon known as P. ciliata var. hibiscifolia and all other taxa within section Dysosmia.Conclusions: The entity studied here is distinct enough to warrant recognition at the rank of species as Passiflora hibiscifolia.